2011
DOI: 10.1002/eco.256
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration and land cover transitions: long‐term watershed response in recovering forested ecosystems

Abstract: Changes of the land surface affect the water balance components over seasonal, annual and decadal time scales. This study explored the role of vegetation cover transitions on evapotranspiration in forested watersheds of the North American West. We applied empirical time‐recovery functions describing the impact of forest removal and subsequent regrowth on actual evapotranspiration (AET) or runoff. A generalized function (K‐curve) was adapted to the North American West and tested using three different datasets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A second water balance model (Model II, Eq. 2) therefore added an interception threshold value of 0.5 mm/h (Gash, 1979). The water vapor exchange from the canopy to the atmosphere is assumed to be 0.5 mm/h when P (t)≥0.5 mm/h and I(t) = P (t) when P (t)<0.5 mm/h.…”
Section: Modeling Approach and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…A second water balance model (Model II, Eq. 2) therefore added an interception threshold value of 0.5 mm/h (Gash, 1979). The water vapor exchange from the canopy to the atmosphere is assumed to be 0.5 mm/h when P (t)≥0.5 mm/h and I(t) = P (t) when P (t)<0.5 mm/h.…”
Section: Modeling Approach and Evaluationmentioning
confidence: 99%
“…Jassal et al (2009) found that in a Douglas fir succession initially reduced evapotranspiration (AET) recovered 12 years after disturbance. Brena Naranjo et al (2011) detected a recovery effect on AET in forest chronosequences and on the water balance in various watersheds in the North American West. Although changes in AET exhibited a different timing, a gradual recovery was common for at least 60 years after disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Jassal et al (2009) found that in a Douglas fir succession initially reduced actual evapotranspiration (AET) recovered 12 yr after disturbance. Breña Naranjo et al (2011) detected a recovery effect on AET in forest chronosequences and on the water balance in various watersheds in the North American West. Although changes in AET exhibited a different timing, a gradual recovery was common for at least 60 yr after disturbance.…”
Section: Introductionmentioning
confidence: 96%